Impact of facies and diagenetic variability on permeability and fluid flow in an oolitic grainstone—Pleistocene Miami Oolite. (10th February 2020) - Harris, Paul (Mitch); Purkis, Sam
Abstract: The Miami Oolite of South Florida is representative of a grainstone‐rich carbonate unit that has been surficially karsted, and therefore may be considered as an analogue for subsurface reservoirs/aquifers with 'high' permeability extremes. The deposit can potentially serve to improve a conceptual understanding of heterogeneity as imparted by shallow‐marine facies changes and early meteoric diagenetic modification. Reviewed here are recent studies of the Miami Oolite with the intent to emphasize those key aspects of the facies and early diagenesis that most impact permeability and fluid flow. The Miami Oolite displays the preserved morphology of a fossilized ooid sandbody, even though it has been subaerially exposed in a tropical climate since its deposition approximately 120 kyr bp during the last interglacial highstand. The depositional motif is one of a dip‐oriented, tidal bar belt of shoals and shallow channels fronted by a strike‐oriented barrier bar. The barrier bar comprises cross‐stratified grainstones and locally burrowed grain/packstones, while the tidal shoals and channels are more commonly burrowed pack/grainstones. Surficial karst features (dolines and stratiform caves) have been added during the ca 120 kyr of subaerial exposure, but of more significance is the associated solution‐enhancement of the widespread burrowed facies. Since the Miami Oolite is the uppermost portion of the Biscayne Aquifer, there is also an understanding of fluid flow through the deposit that sheds valuable insight on the larger scale, shallow subsurface plumbing. The pore system comprises matrix pores (interparticle and separate vugs) and touching‐vug macropores that are commonly associated with burrowed [ Ophiomorpha ] intervals. Ground‐penetrating radar, well and flow test data indicate that matrix porosity provides most of the groundwater storage, whereas the touching vug macropores account for the majority of flow. The dolines and shallow caves seem to be sufficiently spaced as to generally not be in direct connection, with the result that they are less important in terms of regional flow than the prevailing pore system. Abstract : Examples of the porous burrowed‐mottled facies from outcrops (A, B) and cores (C, D). As discussed in the text, Ophiomorpha may be associated with substantial levels of touching‐vug macropores and permeability.